Participation of Tribal farmers in Vegetable Cultivation - Rajesh Kumar,; B.S Arya,; Sunil Arya, (Journal of Agricultural Extension Management, 2025)
Tribal women are mainly concerned with kitchen gardening where they grow all types of vegetables in the form of mixed cropping. Women's participation in vegetable growing goes up to 98 percent. Males are generally engaged in crop cultivation, arrangement of inputs from the market etc. Keeping in view the vital role of women in vegetable cultivation in Meghalaya and Arunachal Pradesh